Conservative management of massive rivaroxaban overdose: A case report and literature review - Alireza Ghodsi (Wiley, 2021)
Abstract In the cases of acute rivaroxaban overdose, conservative management without prothrombin complex concentrate or other coagulation factors may be sufficient if renal function is normal and there is no bleeding.